Effects of progressive muscle relaxation on stress, anxiety, and depression in university students: a quasi-experimental controlled trial - Nurmina Nurmina; Tsania Zelfina; Yolivia Irna Aviani; Devi Rusli; Mardianto Mardianto; Afdal Afdal (Jurnal Konseling dan Pendidikan, 2026)
Stress, anxiety, and depression are prevalent and co-occurring conditions among university students that significantly impair academic functioning and overall well-being. Progressive Muscle Relaxation (PMR) has theoretical and empirical support as a psychophysiological intervention targeting somatic arousal, but evidence from Indonesian university contexts examining all three outcomes simultaneously remains limited. This quasi-experimental study employed a two-group pretest–posttest design to examine the effects of a five-day PMR intervention on stress, anxiety, and depression among psychology students at a public university in West Sumatra, Indonesia. A total of 60 participants meeting inclusion criteria of high or very high DASS-42 scores were assigned to an experimental group (n = 30) or a no-intervention control group (n = 30). Outcomes were measured using the Indonesian-adapted DASS-42. Normality was assessed using the Shapiro–Wilk test; stress and anxiety met normality assumptions and were analyzed using paired-sample t-tests, while depression in the experimental group showed a severe normality violation at posttest (W = .882, p = .002) and was analyzed using the Wilcoxon signed-rank test. The experimental group demonstrated statistically significant reductions in stress (M: 29.63 to 22.10, d = 0.84), anxiety (M: 25.17 to 18.37, d = 0.78), and depression (M: 22.57 to 14.47, r = .54), all p < .001, reflecting large to medium-to-large effect sizes. The control group showed non-significant changes across all outcomes. However, the absence of between-group statistical comparisons, follow-up data, and feasibility metrics limits the strength of causal and practical conclusions. Future research should employ randomized controlled designs with active comparison conditions and follow-up assessments to establish the durability and specificity of PMR effects.